Heavy metals uptake by floating aquatic plants and its recovering pathways - Quek, Yen Ying (2022)
Recently, water pollution with heavy metals has become a serious environmental concern due to their hazardous properties. Since conventional water remediation techniques are generally expensive and non-environmentalfriendly, phytoremediation has gained increasing attention from worldwide researchers and scientists due to its cost-effectiveness and environmental friendliness. This study included reviewing numerous journal articles to demonstrate the efficiency of phytoremediation by aquatic plants. Phytoextraction and phytofiltration were the two main mechanisms accounting for soil and water remediations. Moreover, floating aquatic plants such as duckweed, water lettuce, water hyacinth, and watermoss were regarded as accumulator plants due to their great capability in absorbing the metal ions by their roots and further translocating the metal ions to the aerial parts. This study was performed in six steps: review planning, literature searching, literature screening and scanning, data collection, data analysis, and report writing. Furthermore, the parameter study findings revealed that the optimum solution pH and temperature range that favoured the metal uptake by plants were pH 4 and 30 ℃, respectively. The metal uptake increased with increasing exposure duration, initial metal concentration, and the addition of chelating agents. Opposingly, it decreased with increasing water salinity and the presence of other metals such as zinc (Zn) in the solution. The absorption kinetics of the plants fitted well to the first order kinetic, demonstrating a linear relationship between metal uptake with time. Besides, the postharvested biomass disposal methods were studied. The advantages of biomass disposal methods are to reduce water content, volume, and weight of the biomass, minimize transportation costs, and recover toxic metals from the biomass. Lastly, biosorption of heavy metals by most dead aquatic plants demonstrated the pseudo-second order kinetic and fitted well to the Freundlich model, indicating that multilayer chemisorption of metal ions was governing. In short, phytoremediation is a promising green water remediation approach. However, further research is necessary to enhance its practicability and performance at large-scale implementation.